Dexmedetomidine for intraoperative sedation in a severe Chronic obstructive pulmonary disease patient for lower limb amputation under regional anesthesia - A novel choice - Sharma, Anubhav; Basnet, Madindra; Pradhan, Bishwas (Journal of Society of Anesthesiologists of Nepal, 2015)
The effective management of sedation and analgesia in severe chronic obstructive pulmonary disease patients provides a challenge to the anaesthesiologists and critical care practitioners. Choosing the appropriate agent or combination of agents for sedation is crucial in order to alleviate noxious stimuli, stress and anxiety while minimizing the risk of adverse events. We selected epidural anaesthesia and dexmedetomidine to preserve spontaneous breathing and obtained appropriate sedative and analgesic effect without causing respiratory depression and hemodynamic changes in a patient diagnosed to have chronic obstructive pulmonary disease undergoing femoral to tibial bypass with amputation of right foot. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 34-36